Travail et santé dans la sociologie industrielle de Max Weber - Pierre Desmarez; Pierre Tripier (La Nouvelle Revue du Travail)
In 1907, Max Weber began drafting a manual aimed at researchers involved in a vast survey of industrial work. The following year, he started a detailed study of the factors influencing the productivity of workers employed in a textiles factory, specifically scrutinising occupational health issues (like fatigue) through the prism of productive efficiency. Weber’s focus went beyond a mere consideration of worker characteristics to include forms of cooperation, remuneration and context. By so doing, he trailblazed a new path differing from earlier laboratory studies of worker fatigue.